2010
DOI: 10.2193/2008-065
|View full text |Cite
|
Sign up to set email alerts
|

River Otter Latrine Site Selection in Arid Habitats of Western Colorado, USA

Abstract: River otters (Lontra canadensis) select specific habitat features when establishing latrines, but no studies have described latrine features in arid and semiarid environments. We developed a model describing those habitat features that influence otter latrine site selection on rivers in arid and semiarid watersheds of western Colorado, USA. River otters selected latrine sites with the presence of beaver (Castor canadensis) activity, large prominent rocks, adjacent to deeper water, with shading over the site, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…First, our observed site-specific habitat measurements have shown that when establishing a latrine in all river reaches, river otters selected for similar features, namely high overstory and grass cover, moderately sloping banks, and relatively deep pools. These features have been previously described as suitable for river otters in western streams and lakes (Crait and Ben-David, 2007;DePue and Ben-David, 2010). As indicated by our habitat modeling, the NF had the highest availability of overstory and grass cover at the landscape level compared with the other two reaches.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…First, our observed site-specific habitat measurements have shown that when establishing a latrine in all river reaches, river otters selected for similar features, namely high overstory and grass cover, moderately sloping banks, and relatively deep pools. These features have been previously described as suitable for river otters in western streams and lakes (Crait and Ben-David, 2007;DePue and Ben-David, 2010). As indicated by our habitat modeling, the NF had the highest availability of overstory and grass cover at the landscape level compared with the other two reaches.…”
Section: Discussionsupporting
confidence: 70%
“…Errors using the TEV method were generally higher, but showed similar trends (Table B1). These error rates are higher than other studies in this region (Hayes et al, 2014), but adequate for quantification of habitat features important for river otters (i.e., overstory cover; Crait and Ben-David, 2007;DePue and Ben-David, 2010).…”
Section: Habitat Prey Availability and Disturbancementioning
confidence: 67%
See 1 more Smart Citation
“…River otters have the ability to adapt to a wide variety of habitats and their associated prey species (Melquist and Hornocker, 1983;Dubuc, 1987;Newman and Griffin, 1994;Reid et al, 1994;LeBlanc et al, 2007;Cote et al, 2008;DePue and Ben-David, 2010;Stearns and Serfass, 2011). At Emiquon, fish were the dominant prey type as they often are throughout the range of otters, but crayfish were significantly more important than was expected.…”
Section: Discussionmentioning
confidence: 99%
“…River otters are commensal with North American beavers (Castor canadensis) which provide a variety of important habitats for otters, through their environmental modification, including abundant aquatic food sources from the pooled water, stable water source, plant cover, den, and resting sites (Newman and Griffin, 1994;Dubuc, 1987;LeBlanc et al, 2007;DePue and Ben-David, 2010). The most important of these habitat features is food availability, but shelter availability limits how long an area is used (Melquist and Hornocker, 1983).…”
Section: Introductionmentioning
confidence: 99%